2018
DOI: 10.3892/or.2018.6937
|View full text |Cite
|
Sign up to set email alerts
|

The role of ZBTB38 in promoting migration and invasive growth of bladder cancer cells

Abstract: Bladder cancer is the most common malignancy of the urinary tract, and ~50% of patients with bladder cancer experience recurrence and metastasis. The results of mass spectrometry revealed that the expression of zinc finger and BTB domain-containing 38 (ZBTB38) was higher in highly aggressive human bladder cancer 253J B-V cells compared with in the less aggressive bladder cancer 253J cells. However, the association between ZBTB38 and bladder cancer is currently not well defined, and the association of ZBTB38 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Regarding the oncogenic function of these genes, only HDAC4 had been reported before to be involved in lymphoma and leukemia 31,32 . Our results thus provide novel candidate genes for research of their function in NHL, particularly those genes like ANKS1B , 33‐35 ZBTB38 36‐39 and CCDC91 40 that have been reported to play an oncogenic role in other cancers. Given their increased expressions in NHL, the pathological functions of these three genes in NHL are worth further investigation.…”
Section: Discussionmentioning
confidence: 64%
“…Regarding the oncogenic function of these genes, only HDAC4 had been reported before to be involved in lymphoma and leukemia 31,32 . Our results thus provide novel candidate genes for research of their function in NHL, particularly those genes like ANKS1B , 33‐35 ZBTB38 36‐39 and CCDC91 40 that have been reported to play an oncogenic role in other cancers. Given their increased expressions in NHL, the pathological functions of these three genes in NHL are worth further investigation.…”
Section: Discussionmentioning
confidence: 64%
“…As a transcription factor, ZBTB38 is involved in cell regulation, proliferation and apoptosis, whereas functional de ciency of ZBTB38 induces the human neuroblastoma cell death [12]. Moreover, ZBTB38 play an oncogenic role in neuroblastoma and bladder cancer [12,13]. Based on these studies, we hypothesized that FAM83H-AS1 may be partially required for ZBTB38 to exert its oncogenic effect in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that as a transcription factor, ZBTB38 is involved in human neuroblastoma cell regulation, proliferation and apoptosis, whereas knockdown of ZBTB38 induces neuroblastoma cell death potentially [12]. ZBTB38 may promote cell migration and invasion of bladder cancer cells via up-modulation of Wnt/β-catenin pathway [13]. The above ndings suggest that ZBTB38 may function as an oncogene in some tumors.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Results from a genome-wide association study (GWAS) done on prostate cancer patients revealed that polymorphisms in ZBTB38 gene increase the risk of developing prostate cancer in men (64). In bladder cancer cells, ZBTB38 increased cell migration, invasion, and metastasis via regulating genes belonging to the Wnt/β-catenin signaling pathway but decreased bladder cancer cell proliferation (65). Depletion of ZBTB38 increases the cytotoxic ability of DNMT inhibitors in different solid and hematological cancer cell lines by increasing the expression of Cyclin-Dependent Kinase Inhibitor 1C ( CDKN1C ) which opens up a new avenue to increase the therapeutic response to DNMT inhibitors (189).…”
Section: Classification Of Mbpsmentioning
confidence: 99%